Protection from environmental enteric dysfunction and growth improvement in malnourished newborns by amplification of secretory IgA - Perruzza, Lisa; Rezzonico Jost, Tanja; Raneri, Matteo; Gargari, Giorgio; Palatella, Martina; De Ponte Conti, Benedetta; Seehusen, Frauke; Heckmann, Julia; Viemann, Dorothee; Guglielmetti, Simone; Grassi, Fabio (Cell reports. Medicine, 2024)
Environmental enteric dysfunction (EED) is a condition associated with malnutrition that can progress to malabsorption and villous atrophy. Severe EED results in linear growth stunting, slowed neurocognitive development, and unresponsiveness to oral vaccines. Prenatal exposure to malnutrition and breast feeding by malnourished mothers replicates EED. Pups are characterized by deprivation of secretory IgA (SIgA) and altered development of the gut immune system and microbiota. Extracellular ATP (eATP) released by microbiota limits T follicular helper (Tfh) cell activity and SIgA generation in Peyer’s patches (PPs). Administration of a live biotherapeutic releasing the ATP-degrading enzyme apyrase to malnourished pups restores SIgA levels and ameliorates stunted growth. SIgA is instrumental in improving the growth and intestinal immune competence of mice while they are continuously fed a malnourished diet. The analysis of microbiota composition suggests that amplification of endogenous SIgA may exert a dominant function in correcting malnourishment dysbiosis and its consequences on host organisms, irrespective of the actual microbial ecology. [Display omitted] •Malnourishment of prospective dams replicates EED in pups•Malnourished mothers and offspring are characterized by SIgA impoverishment•An apyrase-releasing live biotherapeutic induces SIgA amplification in pups•SIgA amplification improves pups’ growth and intestinal immune competence Environmental enteric dysfunction (EED) is a causal factor of stunting and neurocognitive defects in malnourished infants. Perruzza et al. develop a bioengineered live biotherapeutic able to restore intestinal immune functions in offspring from malnourished dams. The resulting amplification of mucosal secretory IgA ameliorates EED and partially restores pups’ growth.